PENINGKATAN PROSES DAN HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN DENGAN MENGGUNAKAN PERMAINAN MONOPOLI DI SMAN 12 BUNGO - Maria Susanti (Jurnal Tunas Pendidikan, 2023)
This research is a classroom action research that conducted to improve the students’ learning processes and students’ achievement in civics education learning by using Monopoly game learning media. This action was conducted in to two cycles, where each cycle saw an increase in learning processes and outcomes. This increase also occurred in student learning achievement which continued to increase from the pre-cycle to the first cycle and continued to increase in the second cycle. Before the implementation of the action, only 35.7% of all students passed the KKM. Then, after the implementation of the action, in the first cycle the average student learning outcomes increased. The percentage increased by 28.4% from the pre-cycle, i.e. 64.2% of all students got grades that passed the KKM (70). Then, the learning outcomes of students returned to increase in the second cycle. Based on the test results of students, students who obtained completeness were 22 out of 28 students if the percentage was 78.5%.